PEDAGOGICAL AND PSYCHOLOGICAL CHARACTERISTICS OF GENIOLOGY ASSIGNMENT IN YOUNG PEOPLE - Ganieva Khalimakhon Akhmatkhonovna (Galaxy International Interdisciplinary Research Journal, 2021)
Pedagogical and psychological features of the pursuit of genius in young people. This article analyzes the pedagogical and psychological features, problems and current issues of the pursuit of genius in today’s youth.